2017
DOI: 10.1038/ja.2017.1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular beacons to identify gifted microbes for genome mining

Abstract: Microbial genome mining is a promising technology that is revitalizing natural product discovery. It is now well documented that many bacteria with large genomes, particularly actinomycetes, encode many more secondary metabolites (SMs) than was previously known from their expressed secondary metabolomes. There are effective bioinformatics tools for counting the numbers and nature of SMs, and determining the total coding capacity from finished microbial genomes. However, these methods do not translate well to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 58 publications
(82 reference statements)
0
24
0
1
Order By: Relevance
“…A large number of contigs in the genome assembly can lead to BGCs, especially PKS-I and NRPS, to be broken across pieces and not being identified by available software and tools. A great example of such issue was demonstrated by Baltz who showed that draft genomes containing large NRPS/PKS-I genes were incorrectly assembled due to being largely fragmented which resulted in overestimation of such BGCs by antiSMASH 3.0 [57]. However, since then, new updated versions of antiSMASH have been released in which the location of the gene cluster close to the contig edge is flagged.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of contigs in the genome assembly can lead to BGCs, especially PKS-I and NRPS, to be broken across pieces and not being identified by available software and tools. A great example of such issue was demonstrated by Baltz who showed that draft genomes containing large NRPS/PKS-I genes were incorrectly assembled due to being largely fragmented which resulted in overestimation of such BGCs by antiSMASH 3.0 [57]. However, since then, new updated versions of antiSMASH have been released in which the location of the gene cluster close to the contig edge is flagged.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, resistome is now identified in almost every microbial community, including soil, activated sludge, human gut and oral microbiomes, and animal gut microbiomes [ 539 , 540 ]. On the other hand, it is now extremely difficult to find an effective antibiotic against resistant pathogenic bacteria, although every effort has been taken to discover new antibiotics [ 541 , 542 , 543 ]. One of the steps to solve this problem is to know precisely the mechanisms of drug resistance in the various kingdoms once more.…”
Section: Discussionmentioning
confidence: 99%
“…The advances in genome sequencing of extremophilic microorganisms have allowed us to provide a comprehensive understanding of their applications [93][94][95]. Moreover, microbes with large genomes, usually inhabiting complex harsh environments, can produce a vast array of secondary metabolites [96,97].…”
Section: Biotechnological Potential Of Prokaryotes Inhabiting Dhabsmentioning
confidence: 99%